Cybercrime Awareness Phishing Email Using Secure Socket Layer as an Interpretation of Information Security - Kotim Subandi; Dinar Munggaran A; Victor Ilyas Sugara; Adriana Sari Aryani; Hermawan T (Program Studi Ilmu Komputer, Universitas Pakuan, 2025)
Abstract. Email phishing is a fraudulent technique used by cybercriminals toobtain sensitive information through emails that appear legitimate but havemalicious purposes. Information security has become a crucial aspect in theincreasingly developing digital world, especially along with the increasing threatof cybercrime, such as email phishing. In this context, implementing Secure SocketLayer (SSL) is one solution to increase awareness and mitigate risks againstphishing attacks. SSL, which is a security protocol for data encryption, can helpprotect digital communications by authenticating servers and encrypting datasent, thereby reducing the potential for misuse of personal data sent via email.This research aims to examine the role of SSL in providing protection against emailphishing and increasing user awareness regarding the importance of informationsecurity in the use of digital technology. Through an information securityinterpretation approach, this study suggests that SSL can serve as an effectivebarrier in reducing the risk of phishing attacks and increasing the level of usertrust in the emails received. Therefore, it is important for individuals ororganizations to understand and apply information security principles such as theuse of SSL to maintain the integrity and confidentiality of data exchanged online